Effect of Direction and Tension of Kinesio Taping Application on Sensorimotor Coordination - Bravi, R.; Cohen, E. J.; Quarta, E.; Martinelli, A.; Minciacchi, D. (International Journal of Sports Medicine, 2016)
The present study investigates whether different directions and tensions of Kinesio® Tex tape (KT) application differently influence the precision of sensorimotor synchronization, defined as the ability to coordinate actions with predictable external events. 10 healthy participants performed sets of repetitive wrist flexion-extensions synchronized to a series of paced audio stimuli with an inter-onset interval (IOI) of 500 and 400 ms. KT was applied over the wrist and finger extensor muscles. 2 facilitatory (light and moderate tension) and one inhibitory KT applications were used in different sessions. Standard deviation of the asynchrony (SDasy) and percentage difference of SDasy were calculated and compared across KT and the no-KT control cases. Direction and tension of KT application did not differently influence the ability to coordinate rhythmic movements to an auditory stimulus. However, compared with the no-KT control case, SDasy decreased significantly in all KT cases in both 500- and 400-ms IOI. Independent of direction/tension, the effect of KT on improving sensorimotor synchronization is likely associated with variations in the nature of the neuro-anatomical constraints determining the control of voluntary movement. KT is then proposed to be tested on sensorimotor disorders associated with intense repetitive exercise to check for regaining effective motor control.
Keywords: elastic taping; sensorimotor synchronization; rhythmic motor skills; motor control; upper limbs